An anti-SARS-CoV-2 quantitative study to determine the effect of time on the antibody titre, post-vaccination - Meyer, Burnet Adriaan (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.